Incumbency and expectations of fiscal rule compliance: Evidence from surveys of German policy makers - Friedrich Heinemann; Eckhard Janeba; Maximilian Todtenhaupt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
In this paper, we analyze politicians' expectations about future compliance with a fiscal rule, and in particular the dependence of the expectations on their role in parliament (opposition vs. incumbent government coalition). In addition, we explore how opposition and incumbent politicians adjust their expectations differently when new information on the fiscal environment becomes available. Answering these questions helps in understanding whether long-term policy goals like sustainable debt levels can be reached despite changes of executive power between parties. We study these questions in the context of the German debt brake, which became a constitutional provision in 2009 but is binding for the sub-national states from 2020 onwards only. We analyze compliance expectations of parliamentarians of all 16 German state parliaments based on a unique survey, conducted in 2011/2012 and 2014/16. We find a strong incumbency effect, making politicians from the governing coalition more optimistic than those from the opposition. A negative fiscal shock has little effects on the former, but a strongly negative one on the latter.
Keywords: H63; H74; 330; fiscal rules; incumbency; fiscal policy; political economy